Decreased Levels of Histidine-Rich Glycoprotein (HRG) and Increased Levels of Free Plasminogen in Women on Oral Contraceptives Low in Estrogen - Jespersen, Jørgen; Kluft, Cornelis (Thrombosis and Haemostasis, 1982)
Determinations by immunologic methods of histidine-rich glycoprotein (HRG) and plasminogen, were made in plasma samples collected during one normal or hormone induced cycle in 15 young, normal women and in 11 women using oral contraceptives with 30 μg ethinyl estradiol and 150 μg levo-norgestrel. The hormone group showed an increase in plasminogen level to about 150% of normal, while the concentration of HRG was decreased to about 75% of normal. This resulted in a considerable relative increase in the concentration of free plasminogen in the hormone group (calculated from the equilibrium: HRG·plasminogen ⇌ HRG + plasminogen, using KD = 1.0 μM), representing a doubling of that in the normal group. Hence, more plasminogen is available for binding to fibrin and activation in the hormone group.
Keywords: Histidine-rich glycoprotein; Oral contraceptives; Plasminogen